Green Algorithms: Unveiling the Role of AI in Shaping More Sustainable Consumers - Suherdi; Ikhwan, Muhammad; Munawaroh; Aristanti, Wida; Rulita Nurfaizana, Della; Rahma, Muthya; Abrar, Syaifullah (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
This study aims to analyze the impact of information quality and service quality on customer satisfaction, with customer experience serving as a mediating variable within the context of artificial intelligence (AI)-based digital services. As Jakarta continues to evolve as a digital economic hub, the integration of AI into customer interactions has become crucial, yet it presents challenges regarding information accuracy and user trust. The research employs a quantitative approach, utilizing a survey method conducted among 350 university students in Jakarta who are active users of AI-driven digital platforms. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that both information quality and service quality have a significant positive influence on customer experience. Empirical results confirm that customer experience acts as a significant mediator in the relationship between the independent variables and customer satisfaction. The research model yielded an R-square value of 0.64 for customer satisfaction, demonstrating strong predictive power. These results emphasize that providing accurate information and responsive service is essential for creating a satisfying digital experience in the AI era. Practical implications suggest that digital service providers must prioritize the quality of automated system interactions to build sustainable relationships with consumers.